Towards the Formation of Genuine European Parties? Examining and Comparing the Cases of DiEM25 and Volt Europa - Panayotu, Panos; Katsambekis, Giorgos (PARTECIPAZIONE E CONFLITTO, 2023)
The 2019 European Parliament (EP) election saw the participation of two transnational parties: DiEM25 and Volt Europa. Both seek to democratise the European Union (EU) by engaging with European institutions and mobilising their supporters across member states, putting the EU’s democratic deficit at the centre of their endeavour. They consider the European space as their primary field of appeal and mobilization, adopting a transnational conception of ’the people’ as the source of democratic legitimacy. This paper explores the potential of genuine pan-European parties in increasing public contestation and inclusiveness at the European level and in democratising EU politics by treating DiEM25 and Volt as prototypical cases. Through a comparative analysis, we highlight the novelties of the two parties in relation to existing ’Europarties’ and assess how these respond to deficiencies related to the democratic deficit. We conclude by reflecting upon what DiEM25 and Volt reveal about the potentials and challenges of ’transnationalising’ EU politics.